Sleep quality and food intake of high school students - Carvalho, Ana Sofia Coelho (2019)
Poor sleep quality is associated with increased food intake and poor diet quality [1]. People with lack of sleep show a positive correlation. between free time and food intake and also experience hormonal and brain changes that drive the intake of food with high calorific value [1-3]. In addition, scientific research has shown a healthy and balanced diet to positively influence the quality of sleep [1]. Objective The present study was set out to assess the sleep quality of high school students in Bragança county, and its association with food intake. Methods The study used non-experimental, analytical and transversal methodology, of epidemiological character and with a quantitative approach. It was intended to carry out the study in a population of 862 high school students. However, due to consent being required from both legal guardians and students, a smaller sample of 345 students was obtained. The data was collected in May 2017 through a questionnaire that included the Pittsburgh Sleep Quality Index (PSQI), validated for the Portuguese population. Results Throughout the study and following PSQI analysis, it was concluded that 39.71% (n = 137) of participants showed poor quality of sleep (PSQI > 5 points). The correlation between sleep quality and food intake was assessed and a statistically significant association was found between the quality of sleep and the intake of snacks (X2 = 17.144; p = 0.000), sugary products (X2 = 18.603; p= 0 .000), fast-food (X2 = 12.353; p = 0.002) and ready meals (X2 = 14.852; p = 0.000). The risk of suffering from poor sleep quality is higher in young populations who frequently eat snacks ([OR]: 2.811; 99%), sugary products ([OR]: 1.901; 95%), fast-food ([OR]: 4.000; 99%) and ready meals ([OR]: 5.621; 95%) in comparison with young populations who rarely eat this sort of food. The sleep quality is also significantly related with the number of meals young people have in a day (X2 = 7.580; p = 0.023). The risk of having poor quality sleep is 2.240 times higher in young people who rarely eat 4-6 meals a day. Conclusions A correlation between sleep quality and food intake in the sampled students was seen. The risk of having poor quality of sleep is higher in students who frequently eat a high calorie diet and also in students who rarely have 4-6 meals a day. There are several connections between sleep quality and eating habits. Sleep promotion and its connection with standard diets should be included as an essential part of community empowerment for health-promoting lifestyles [1,4,5].